Effects of the inhalation of high oxygen concentration on free radicals metabolism and oxidative, antioxidative capability of erythrocyte after intensive exercise - Huang, J.; Li, H.; Xiao, G. Q.; Qiu, Z. Y.; Su, S.-X.; Xie, W.-M. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of our study was to investigate the effects of inhalation of high oxygen concentration on free radicals metabolism and oxidative capacity of erythrocyte after intensity exercise.